Hubungan Spiritualitas dengan Kesejahteraan Psikologis pada Remaja di Madrasah Aliyah Unggulan Amanatul Ummah Surabaya - Ellyza Audia; Dya Sustrami; Nur Muji Astuti (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2025)
Introduction: A high spiritual condition is something to achieve good psychological well-being. Psychological well-being can be equated with mental health. Adolescents who have good mental health will have all aspects of their psychological well-being fulfilled. Objectives: The study aim to analyzed the relationship between spirituality and psychological well-being in adolescents at the Madrasah Aliyah Unggulan Amanatul Ummah Surabaya Methods: This research design used an analytical observational design approach Cross Sectional. This research was conducted at Madrasah Aliyah Unggulan Amanatul Ummah Surabaya with a population of 200 respondents, using the technique Probability Sampling with approach Stratified Random Sampling The results obtained were 133 samples. Instrument used Daily Spiritual Experience Scale (DSES) to measure spirituality and Ryff Psychological Well-being Scale (RPWS) to measure psychological well-being. Results:  The research results showed that the majority of respondents had high spirituality and moderate psychological well-being. Statistical test results using Spearman Rho The results obtained were ρ 0.000 (ρ≤0.05), there was a relationship with a correlation coefficient of r 0.348, which means there is a sufficient relationship (0.26–0.50) between the spirituality variable and psychological well-being. Conclusions:  High spirituality is able to provide good psychological well-being in adolescents, so that spirituality can be increased and monitored to create high psychological well-being in adolescents .